The ideological evolution of human resource management : a critical look into HRM research and practices - Itani, Sami (Critical management studies (Series), 2017)
This bookis a pioneering work that maps out the ideological evolution of HRM researchand practices, with a particular focus on our contemporary era of multinationalcorporations. It explores the ideological evolution of Human ResourceManagement (HRM) from the 1950s to the present day and maps out the developmentof HRM research and practices from a Critical Theory perspective. Its findingsopen up avenues for metatheoretical development within the HRM research fieldand provide employees under modern capitalism with emancipatory awareness.Both thetheoretical framework and the empirical findings of this study will be ofinterest to HRM researchers as well as management researchers of all epistemologicalbackgrounds, particularly those working within Critical Management Studies. Thiswork will also appeal to teachers and students, and it could serve as a textbookfor a number of postgraduate level courses, including Organization Theory,Critical Management Studies, Human Resource Management, Business History,Sociology of Management, and Critical Theory.